1994
DOI: 10.1002/aqc.3270040206
|View full text |Cite
|
Sign up to set email alerts
|

Marine reserve site selection along the Abel Tasman National Park coast, New Zealand: Consideration of subtidal rocky communities

Abstract: ABSTRACT1. At present, marine reserves do not represent the full range of community types throughout New Zealand.2. To assist with the placement of a marine reserve along the Abel Tasman National Park coast (northern South Island), dominant subtidal laminarian and fucoid algae, echinoids and herbivorous molluscs were quantitatively investigated. Results from 100 quadrats collected from 19 random transects at six selected sites showed that algae and grazer assemblages varied between granite and limestone substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…It has been a marine reserve since November 1993, covers 1835 ha, and extends 10.5 km alongshore and 1852 m offshore (1 nautical mile) (Department of Conservation, 2001b). The subtidal environment has been described in Davidson and Chadderton (1994). Briefly, the reef comprises granite boulders up to 5 m high, which provide extremely high rugosity and the reef slopes to meet muddy sand at depths of about 12-15 m in most areas.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been a marine reserve since November 1993, covers 1835 ha, and extends 10.5 km alongshore and 1852 m offshore (1 nautical mile) (Department of Conservation, 2001b). The subtidal environment has been described in Davidson and Chadderton (1994). Briefly, the reef comprises granite boulders up to 5 m high, which provide extremely high rugosity and the reef slopes to meet muddy sand at depths of about 12-15 m in most areas.…”
Section: Study Areamentioning
confidence: 99%
“…The creation of numerous marine reserves throughout New Zealand has offered the opportunity to investigate the populations of many species in unharvested situations (Creese and Cole, 1995;Department of Conservation, 2001a). Few published studies from marine reserves in more southern areas exist (but see Davidson and Chadderton, 1994;Cole et al, 2000;Davidson, 2001) despite there being six reserves in the South Island (Creese and Cole, 1995;Department of Conservation, 2001a). Comparisons of reserve effects among areas for the same species are rare (but see Edgar and Barrett, 1999;Kelly et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-four years later, Davidson & Chadderton (1994) reported the persistence of this pattern at Kaiteriteri, and its presence more widely from granite shorelines of the Abel Tasman coastline. However, on the neighbouring limestone shorelines, with the same Evechinus densities (but lower numbers of herbivorous gastropods), the rocky reef was covered in a mixed algal community dominated by Ecklonia and foliose red algae.…”
Section: Discussionmentioning
confidence: 97%
“…Associations between specific species assemblages and rock types occur in many marine habitats at scales that encompass different geographical locations (Davidson & Chadderton 1994, Bavestrello et al 2000, Guidetti et al 2004, Green et al 2012, Liversage & Benkendorff 2013. Similar associations may occur in these South Australian reefs, in which case we would expect that assemblages on control boulders in siltstone and limestone reefs would be significantly different.…”
Section: Q1: Do Assemblages On Siltstone and Limestone Reefs Differ?mentioning
confidence: 92%
“…However, evidence for an effect of rock type on benthic species is sparse. Some studies have found associations between biotic structure and rock type at scales encompassing different geographical locations (Vermeij 1971, Raimondi 1988, Davidson & Chadderton 1994, Holmes et al 1997, Bavestrello et al 2000, Guidetti & Cattaneo-Vietti 2002, Schiaparelli et al 2003, Guidetti et al 2004, Herbert & Hawkins 2006, Green et al 2012). The associations found at this scale, however, have rarely been confirmed at the boulder scale (e.g.…”
Section: Discussionmentioning
confidence: 99%